PENGARUH BEBAN KERJA, KOMUNIKASI DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PADA PT. BPR SINAR KUTA - Ni Luh Tri Dyah Wahyuni; Wayan Sujana; Ni Nyoman Ari Novarini (JUIMA : JURNAL ILMU MANAJEMEN, 2023)
This study aims to determine the effect of workload, communication and competence on employee performance at PT. BPR Sinar Kuta. This research was conducted at PT. BPR Sinar Kuta with a total sample of 40 employees. The method of determining the sample in this study is the saturated sampling method. Data was collected through observation, interviews and questionnaires. The data analysis technique used in this study is linear regression analysis through the SPSS version 25 program. Based on the results of the analysis, this study shows that workload has a negative and significant effect on employee performance at PT. BPR Sinar Kuta. Communication has a positive and significant effect on employee performance at PT. BPR Sinar Kuta. Competence has a positive and significant effect on employee performance at PT. BPR Sinar Kuta.